Perilaku Pembelian Kosmetik Secara Online Selama Pandemi - Ni Made Dhian Rani Yulianti; Putu Nita Oktaviani; I Made Sindhu Yoga; Ni Nyoman Sri Wisudawati; Putu Ratna Juwita Sari (Jayapangus Press, 2021)
During the Covid-19 pandemic, consumers mostly do facial and body care at home, and online transactions are no exception. Cosmetic products are risky products if we do not try them first because of differences in skin type or face shape. Yet, why are Millennial Generation women confident about buying them online? The purpose of this study was to confirm whether the factors of merchandise, price, trust and online purchasing experience were the factors that consumers consider to buy cosmetic products online. Data that has been obtained by distributing questionnaires to 100 respondents by purposive sampling were analyzed using factor analysis techniques with the help of SPSS for Windows version 24 software. The results of data analysis only formed two factors from the four suspected factors. The first factor was called the Online Shopping Motivation factor which consists of 12 indicators and the second factor was called the trust factor which consists of seven indicators.